2018
DOI: 10.2188/jea.je20170048
|View full text |Cite
|
Sign up to set email alerts
|

A Point System for Predicting 10-Year Risk of Developing Type 2 Diabetes Mellitus in Japanese Men: Aichi Workers’ Cohort Study

Abstract: BackgroundRelatively little evidence exists for type 2 diabetes mellitus (T2DM) prediction models from long-term follow-up studies in East Asians. This study aims to develop a point-based prediction model for 10-year risk of developing T2DM in middle-aged Japanese men.MethodsWe followed 3,540 male participants of Aichi Workers’ Cohort Study, who were aged 35–64 years and were free of diabetes in 2002, until March 31, 2015. Baseline age, body mass index (BMI), smoking status, alcohol consumption, regular exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Alcohol Consumption and T2D. All 8 studies included in the meta-analysis evaluated the association between alcohol intake and the T2D risk [12][13][14][15][29][30][31][32]. The summary RRs showed that alcohol intake, compared with no alcohol intake, was not associated with risk of T2D among Asian men (RR = 1:01, 95% CI: 0.88-1.15, p = 0:931; Q statistic, p < 0:001; I 2 = 76%) ( Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Alcohol Consumption and T2D. All 8 studies included in the meta-analysis evaluated the association between alcohol intake and the T2D risk [12][13][14][15][29][30][31][32]. The summary RRs showed that alcohol intake, compared with no alcohol intake, was not associated with risk of T2D among Asian men (RR = 1:01, 95% CI: 0.88-1.15, p = 0:931; Q statistic, p < 0:001; I 2 = 76%) ( Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-Analysis. Eight cohorts were included in the dose-response analysis, estimating the relationship between alcohol intake and risk of T2D [12][13][14][15][29][30][31][32]. There was a nonlinear dose-response relationship between alcohol intake and T2D risk among Asian men (p nonlinearity = 0:003) (Figure 3).…”
Section: Dose-responsementioning
confidence: 99%
See 3 more Smart Citations